Let it reign: The new water paradigm for global food security - Stockholm International Water Institute; International Food Policy Research Institute; International Union for Conservation of Nature; International Water Management Institute; Lundquist, Jan; Falkenmark, Malin (Stockholm International Water Institute, 2005)
Let it Reign highlights key facts, conditions and trends regarding water aspects of food production, consumption and ecological sustainability. It presents policy recommendations within governance, capacity building/awareness raising and financing in order to improve water productivity and increase the possibility to produce the food needed, improve diets, and raise consumer awareness – all in an equitable and ecologically sustainable manner.